A Novel Methodology for Estimating the Capacity and Level of Service for the New Mega Elliptical Roundabout Intersection. (12th March 2020) - Mohamed, Ahmed I. Z.; Ci, Yusheng; Tan, Yiqiu
Abstract : Mega elliptical roundabout is a new intersection on rural multilane highways. This intersection was developed in a previous paper using simulation data, and the authors found that it is better than interchange (full cloverleaf) in most scenarios of traffic flow. Basically, there are no guidelines or procedures for designing mega elliptical roundabout in AASHTO Green Book, Federal Highway Administration guides, and Highway Capacity Manual. Thus, the purpose of this study is to analyze the traffic operation performance and propose a methodology for calculating the capacity of mega elliptical roundabout and also the level of service by gap acceptance theory. Moreover, this research studied the influence of different values of truck ratios and also different values of a major highway speed on geometric design and traffic operation performance for mega elliptical roundabout. To validate the thoroughness of the proposed methodology, VISSIM simulations were conducted. This research will assist practitioners in determining the appropriate geometric design, assessing mega elliptical roundabout intersections, and making comparisons with other alternatives.